The study of international migration from a gender perspective - Gregorio Gil, Carmen (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
This article is a critical analysis of the different theoretical models applied to the study of migrations from the perspective of the Anthropology of Gender.